A note on the estimation of long-run relationships in panel equations with cross-section linkages - Francesca Di Iorio; Stefano Fachin (Economics: The Open-Access, Open-Assessment E-Journal, 2012)
The authors address the issue of estimation and inference in dependent non-stationary panels of small cross-section dimensions. The main conclusion is that the best results are obtained applying bootstrap inference to single-equation estimators, such as fully modified ordinary least squares and dynamic ordinary least squares. Seemingly unrelated regression estimators perform badly, or are even unfeasible, when the time dimension is not very large compared to the cross-section dimension.
Keywords: C15; C23; C33; 330; panel cointegration; fully modified ordinary least squares; fully modified seemingly unrelated regression; dynamic ordinary least squares; dynamic seemingly unrelated regression; Panel; Kointegration; Schätztheorie; Theorie